COMMUNITY-BASED MANGROVE FORESTS CONSERVATION FOR SUSTAINABLE FISHERIES - Eddy, Syaiful; Ridho, Mohammad Rasyid; Iskandar, Iskhaq; Mulyana, Andy (Journal of Tropical Silviculture, 2016)
The mangrove forests are a type of salt tolerant vegetation, living in tidal zones in tropical and subtropical coastalareas with unique ecosystem that have a strategic function as a connector and counterweight of terrestrial and marineecosystems. Mangrove forests are a productive ecosystem and they have complex functions, such as physical functions,biological functions and socio-economic functions. Fishery resources of mangrove forests are very productive, bothquantitatively and qualitatively, because the mangrove forests act as the natural habitat (spawning, nursery and feedinggrounds) for various species of fish, shrimps and crabs, as well as a source of germplasm and genetic pool. Mangroveforests also provide valuable ecosystem services to coastal communities, tourist attractions, nature conservation,education and research. However, these ecosystems are fragile because it is very sensitive to environmental changes,usually because anthropogenic influences; therefore, it is difficult to be restored. In addition, these ecosystems are soopenly accessible that easily exploited by humans; this can reduce its quality and quantity. Local communities who usemangrove forests and their resources may have considerable botanical and ecological knowledge about their forests.Silvofishery techniques in aquaculture are very suitable for community-based mangrove forests conservation efforts.Silvofishery is an integrated model that considers both economically benefit and conservation.Key words: mangrove conservation, sustainable fisheries, community-based